Skiing efficiency versus performance in double-poling ergometry - Holmberg, L. J.; Ohlsson, M. L.; Supej, M.; Holmberg, H. C. (Computer Methods in Biomechanics and Biomedical Engineering, 2013)
This study is on how leg utilisation may affect skiing efficiency and performance in double-poling ergometry. Three experiments were conducted, each with a different style of the double-poling technique: traditional with small knee range-of-motion and fixed heels (TRAD); modern with large knee range-of-motion and fixed heels (MOD1) and modern with large knee range-of-motion and free heels (MOD2). For each style, motion data were extracted with automatic marker recognition of reflective markers and applied to a 3D full-body musculoskeletal simulation model. Skiing efficiency (skiing work divided by metabolic muscle work) and performance (forward impulse) were computed from the simulation output. Skiing efficiency was 4.5%, 4.1% and 4.1% for TRAD, MOD1 and MOD2, respectively. Performance was 111, 143 and 149 Ns for TRAD, MOD1 and MOD2, respectively. Thus, higher lower body utilisation increased the performance but decreased the skiing efficiency. These results demonstrate the potential of musculoskeletal simulations for skiing efficiency estimations. Volltext unter: http://www.diva-portal.org/smash/get/diva2:444088/FULLTEXT02.pdf